ANALISIS KETERLIBATAN MURID (STUDENT ENGAGEMENT) DALAM PEMBELAJARAN IPAS BERBANTUAN MEDIA DIORAMA DI KELAS III SEKOLAH DASAR - Rizqi, Ardhah Nur; Sutrisno, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe student engagement in learning Natural and Social Sciences (IPAS) assisted by diorama media among third-grade students at SD Negeri Geneng 02. Student engagement is examined through three dimensions: behavioral, emotional, and cognitive engagement. A qualitative descriptive approach was employed, with data collected through classroom observation and semi-structured interviews with the classroom teacher and six students. Data were analyzed through data reduction, data display, and conclusion drawing, and validated through source and technique triangulation. The findings indicate that diorama media increased student’s attention, curiosity, and willingness to participate, particularly at the moment the media was introduced, yet engagement was not evenly distributed among students. Behavioral engagement was reflected in students' attentiveness and task completion, although voluntary participation remained limited for some students. Emotional engagement appeared through expressions of enjoyment and curiosity, while a few students remained emotionally neutral. Cognitive engagement varied more sharply: some students actively connected the diorama to prior experience and constructed reasoned answers, whereas others relied on peers and struggled to elaborate their understanding. This study concludes that concrete media, such as dioramas, can support student engagement in elementary school science learning. However, sustainjng students cognitive engagement requires tergeted teacher guidance, particularly for student who tend to be passive during the learning process.